Identification of dynamic capabilities in open innovation - Aro, Edson Rodrigues de (2021)
Purpose – This study aims to understand the interaction between capabilities inherent in open innovationand dynamic capabilities (sensing, seizing and transforming) as a source of competitive advantage.Design/methodology/approach – Qualitative method and grounded theory were used as guidelines fordata collection and analysis.Findings – The study identifies a set of capabilities in the practice of open innovation related to dynamiccapabilities, which indicates the importance of developing dynamic capability in the strategic management ofinternal and external knowledge in the company.Research limitations/implications – The number of interviewees approached herein do not allowgeneralizations, but the use of grounded theory through various strategies of data collection in the interviewsallowed the triangulation of the data, increasing the credibility, validity and quality of the research.Originality/value – This study presents capabilities identified in open innovation and their relationshipwith dynamic capabilities, identifying the importance of the dynamic capability in the strategic managementof internal and external knowledge in the company as a source of competitive advantage.